Farming systems and poverty : improving farmers' livelihoods in a changing world - Dixon, John (FAO RomeIT, 2001)
Shows how the farming system approach can be used to identify key local, regional and international priorities for the reduction of hunger and poverty. Examines the various strategies open to poor farm families seeking better lives. Discusses how an effective response to these priorities and strategies will require a rethinking of the roles of key stakeholders in the development process.